Research of the thorium purification at monazite refinement processes; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Shagalov V. V. Vladimir Vladimirovich; Sobolev V. I. Vasily Igorevich; Turinskaya M. V.; Malin A. V. (2016, 2016)
Title screen